LEGITYMACJA PROCESOWA UMOWNEGO ZARZĄDCY NIERUCHOMOŚCI - Jędrejek, Grzegorz (Zeszyty Prawnicze, 2016)
Judicial Ticket of a Contractual Real Estate Manager Summary The aim of this article is to explain all doubts referring to a judicial ticket of a contractual real estate manager, which has been legislated in a co-owners’ contract. The issue mentioned above arouses controversy in doctrine but also in judicature. One has adopted a stance in the article, that the real estate manager has got the title to bring the action before the court, which is based on the article 201 of the civil code. A contract connected with entrusting management does not deprive the owners of the rights, including claims consisting of property law. Co-owners allow third parties to carry out entitlements connected with management of a common property. The article consists of three parts. The first one contains concise deliberations about the notion of legitimization. The problem of a judicial ticket of a manager, who was legislated in a contract by co-owners of a common property (article 199-202 of the civil code) was discussed in the second part. The third part of the article is connected with a judicial ticket of a real estate manager, which was mentioned in an act of proprietorship of premises.